Duchowość komunii człowieka z Bogiem - Wejman, Henryk (Wydział Teologiczny, UAM, 2011)
Treść artykułu zorientowana jest na ukazanie istoty i wartości duchowości komunijnej w ujęciu ks. kard. S. Wyszyńskiego. W świetle jego nauczania istota owej duchowości polega na bezgranicznym zaufaniu człowieka Bogu. Jej zaś wartość ujawnia się w skutecznym jego oddziaływaniu na otoczenie, tj. miłosiernej wrażliwości na potrzeby bliźnich i poszanowaniu środowiska ich egzystowania.

The focus of the article is on presenting the essence and values of communion spirituality according to Cardinal S. Wyszyński. Seen from the perspective of his teaching, the essence of this spirituality consists in man's boundless trust in God. Its value unfolds in man's effective influence on his environment, i.e. in his merciful sensitivity to the needs of his neighbors and in respecting the milieu of their existence.
The Spirituality of Man’s Communion with God
Keywords: duchowość; spirituality; jedność duchowa; spiritual union; wiara; faith; modlitwa; prayer; apostolstwo; apostleship